Mesoporous silica ultrathin nanosheet and preparation method thereof
By adding silicon sources at intervals and introducing tetravalent zirconium ions and glycerol, mesoporous silica ultra-thin nanosheets with thicknesses of 50-100 nm were prepared, which solved the problem of excessively long mesoporous channels in the prior art and realized Its application range is expanded by higher specific surface area and more active sites.
Patent Information
- Application Number
- CN202411667457.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to prepare sheet mesoporous silica with thinner thickness, resulting in longer mesoporous channels and unable to provide more active sites and higher specific surface areas.
Mesoporous silica ultra-thin nanosheets were prepared by adding silicon sources at intervals and introducing tetravalent zirconium ions and glycerol, and the thickness was controlled to be between 50 and 100 nm.
The prepared mesoporous silica ultra-thin nanosheets have shorter mesoporous channels, higher specific surface area and more active sites, which improves their application prospects in the fields of catalysis, adsorption, drug loading, etc.
Smart Images

Figure CN119461398A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano-mesoporous materials, and in particular to a mesoporous silicon dioxide ultra-thin nanosheet and a preparation method thereof. Background Art
[0002] Mesoporous silica is widely used in separation, catalysis, sensors, drug delivery and other fields due to its good physical and chemical properties, uniform pore size distribution, high specific surface area, good biocompatibility and good surface modifiability. Flaky mesoporous silica has shorter mesoporous channels, higher specific surface area and can provide more active sites, so it has higher application value in the above-mentioned fields.
[0003] However, the optimal thickness of the sheet-like mesoporous silica prepared by the current technology can only reach 300-350nm, and it is impossible to further reduce its thickness to obtain a sheet-like mesoporous silica with shorter mesoporous channels, higher specific surface area and more active sites. Therefore, the present invention adopts the method of adding silicon source at intervals and introduces tetravalent zirconium ions and glycerol to prepare a mesoporous silica ultra-thin nanosheet. Compared with the currently prepared sheet-like mesoporous silica, its mesoporous channels are shorter, and the shortest can reach about 50nm. Summary of the invention
[0004] In view of the fact that the thickness of the current flaky mesoporous silica can only reach 300-350nm, the present invention provides a method for preparing ultra-thin mesoporous silica nanosheets with a thickness of 50-100nm. Through scanning electron microscope observation, its microscopic morphology is an ultra-thin sheet in the shape of a regular hexagon. The regular microscopic morphology makes the binding sites in its pores evenly distributed, and also significantly improves the specific surface area of the mesoporous silica, while also improving the efficiency of loading and modification.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The invention provides a mesoporous silicon dioxide ultrathin nanosheet, whose microscopic morphology is a regular hexagonal ultrathin sheet observed under a scanning electron microscope.
[0006] Preferably, the thickness of the ultra-thin nanosheet flanks is 49-75 nm.
[0007] The present invention provides a method for preparing the mesoporous silica ultrathin nanosheets described in the above technical solution, comprising the following steps: P123, deionized water, concentrated hydrochloric acid, zirconium oxychloride solution, and glycerol were mixed in a beaker and placed in a water bath for stirring and reaction as a precursor solution; After a period of reaction, a silicon source is added to the stirred precursor solution for the first time to continue the reaction; After a period of reaction, a silicon source is added to the stirring solution for the second time. After a period of reaction, a pre-prepared hydrochloric acid aqueous solution is added to the solution without stopping stirring during the process. After the solution is added and reacted for a period of time, stirring is stopped and the static reaction is started. After the static reaction is completed, the stirring function of the water bath is turned on to fully mix the generated white precipitate with the upper clear solution. The solution is then transferred to a polytetrafluoroethylene liner and placed in a hydrothermal synthesis reactor for hydrothermal treatment. After the hydrothermal treatment is completed, the product is taken out, washed, filtered, and dried. The obtained mesoporous silica is placed in a muffle furnace for calcination to remove the template.
[0008] Preferably, the silicon source is tetraethyl orthosilicate, the mass ratio of the two additions is 3.8-4.3:1, and the total mass of tetraethyl orthosilicate is 4.28g; Preferably, the reaction time of the first addition of the silicon source pre-solution is 12 to 20 minutes; Preferably, the reaction time between the first addition of the silicon source and the second addition of the silicon source is 50 min to 75 min; Preferably, the reaction time before adding the hydrochloric acid aqueous solution is 5 min to 10 min; Preferably, the mass of the hydrochloric acid in the hydrochloric acid aqueous solution is 6.5-7.5 g, and the mass of the deionized water is 95-105 g; Preferably, the reaction time after adding the mixed solution of hydrochloric acid and water is 5 to 10 minutes, and then the stirring is stopped and the reaction is allowed to stand; Preferably, after stopping stirring, the standing time is 3 to 4 hours; The hydrothermal time is 22 to 28 hours, and the hydrothermal temperature is 120 to 140°C; Preferably, the calcination temperature is 550° C. and the holding time is 4 to 6 hours.
[0009] The present invention provides a mesoporous silica ultra-thin nanosheet, which is observed under a scanning electron microscope to be a regular hexagonal and ultra-thin sheet, with a thickness of about 50 nm. The mesoporous silica ultra-thin nanosheet provided by the present invention has a large surface area, adjustable pore size distribution, high pore volume, and the ability to be modified by different functional groups, and also has excellent properties of heat resistance, mechanical tension resistance, and resistance to hydrolysis-induced degradation. Since the introduced zirconium oxychloride inhibits the radial growth of the mesoporous silica, the mesoporous silica is transformed into a thin sheet structure with short pores, and the short pore morphology is conducive to the rapid diffusion of reactant molecules in the pores. Its application degree is improved and its application range is expanded.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: tetraethyl orthosilicate is used as a silicon source, tetravalent zirconium ions and propylene glycol are introduced compared to the existing preparation method of sheet-like mesoporous silica, and tetraethyl orthosilicate is added at intervals; the length of the mesoporous channel of the mesoporous silica ultra-thin nanosheet prepared by this method is significantly shortened, which is more conducive to the rapid transmission of the medium, and at the same time, the shorter pore structure can also provide more active sites for modification and loading, and has broad application prospects in the fields of adsorption of heavy metal elements in wastewater, indoor air purification, catalysis, drug delivery, carbon dioxide capture, biological analysis sample preparation, improvement of pervaporation membranes, etc.
[0011] The present invention provides a method for preparing the mesoporous silica ultrathin nanosheets described in the above technical solution, comprising the following steps: mixing P123, deionized water, concentrated hydrochloric acid, zirconium oxychloride solution, and glycerol in a beaker for reaction, adding a silicon source twice before and after, and then adding a hydrochloric acid aqueous solution for reaction, and removing the template agent after calcination of the product obtained after hydrothermal treatment to obtain the mesoporous silica ultrathin nanosheets. Compared with the short-channel lamellar mesoporous silica prepared by the current technology, its microscopic morphology presents a relatively regular regular hexagonal thin sheet. Not only is the mesoporous channel shorter, but it also has better modification and loading performance. It has broad application prospects in the fields of catalysis, adsorption, and drug loading. The nitrogen adsorption-desorption analysis curve of the ultrathin nanosheet shows that the material has an H1-type hysteresis loop, which is a classic mesoporous structure. Moreover, the preparation method provided by the present invention is simple to operate, has low production cost, is safe and environmentally friendly, is non-toxic, has a short production cycle, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Scanning electron microscope (SEM) image of mesoporous silica ultrathin nanosheets; Figure 2 SEM image of the thickness of mesoporous channels of mesoporous silica ultrathin nanosheets; Figure 3 Nitrogen adsorption-desorption curves of mesoporous silica ultrathin nanosheets. DETAILED DESCRIPTION
[0013] The present invention provides a mesoporous silica ultrathin nanosheet and a preparation method thereof, wherein tetraethyl orthosilicate is used as a silicon source, and the nanosheet refers to a thin sheet whose microscopic morphology is less than 100 nm thick under nanoscale observation with a scanning electron microscope. In the present invention, the thickness of the ultrathin sheet is preferably 65 to 75 nm, and more preferably 49 to 55 nm. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with examples below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0014] The invention provides a method for preparing the mesoporous silica ultrathin nanosheets described in the technical scheme. The method comprises the following steps: mixing P123, deionized water, concentrated hydrochloric acid, zirconium oxychloride solution and glycerol in a beaker and putting the mixture into a water bath for stirring and reacting; adding a silicon source, namely tetraethyl orthosilicate, to the reaction solution, and then continuing the reaction for 1 to 1.5 hours, and then adding tetraethyl orthosilicate to the reaction solution again, and then adding a pre-prepared mixed solution of hydrochloric acid and water after reacting for a period of time, and then continuing the reaction for 5 to 10 minutes and then stopping the stirring, and standing in a water bath at a constant temperature of 30°C for 3 to 3.5 hours to obtain a white suspension, transferring the suspension to a reactor for hydrothermal heating for 24 hours, and then separating, washing, drying and calcining the cooled reactants to remove the template agent to obtain the mesoporous silica ultrathin nanosheets.
[0015] In the present invention, a mixed solution of glycerol and water is used as a solvent, and an organic template P123 is dissolved under the action of the solvent. Due to the presence of the organic template P123, primary silica particles generated after the hydrolysis of tetraethyl orthosilicate gradually grow under the action of the organic template. The traditional growth mode is radial growth, that is, forming a worm-like structure, but the radial growth of mesoporous silica is inhibited under the action of tetravalent zirconium ions in the zirconium oxychloride solution, so the microscopic morphology of the mesoporous silica gradually grows into a sheet; that is, tetraethyl orthosilicate is added at intervals as a silicon source and forms a sheet under the action of the organic template and zirconium ions, the addition of concentrated hydrochloric acid can promote the hydrolysis of the silicon source, and the addition of the organic compound glycerol also limits the radial growth of the mesoporous silica nanosheets to a certain extent, plays a regulating role in the thickness thereof, and further promotes the reactants to form ultra-thin sheets when standing in a water bath. The hydrochloric acid aqueous solution added at last can reduce the concentration of the product, thereby reducing the possibility of its lateral and longitudinal aggregation, so as to achieve the purpose of controlling the thickness of the final product. The obtained white precipitate is subjected to a series of treatments to obtain a finished product.
[0016] The method provided in this embodiment allows the surfactant to dissolve in an acidic organic solvent system, controls the morphology of mesoporous silica by adding a silicon source twice at intervals, further limits the radial growth of mesoporous silica nanosheets and reduces the thickness of the nanosheets by adding a hydrochloric acid aqueous solution again for dilution, and the subsequent separation, washing, calcination and other processes are basically the same as the traditional post-treatment method of mesoporous silica. Therefore, the preparation method has simple steps, the materials are easy to obtain and safe and non-toxic, the product is pure and single, the structure is stable, the cost is low, and it is conducive to industrial production.
[0017] In order to make the surfactant dissolve under acidic conditions and form micelles better, it is necessary to adjust the mixing ratio of glycerol solution and deionized water to provide a template for silica. In a preferred embodiment, the mass ratio of the total mass of deionized water to the mass of glycerol solution is 20:1, so that the surfactant can better form micelles.
[0018] The selected organic template is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer aqueous solution, that is, a 10wt% P123 aqueous solution, and concentrated hydrochloric acid is selected as a catalyst for dissolving the organic template to form micelles and hydrolyzing tetraethyl orthosilicate to form mesoporous silica.
[0019] The tetravalent zirconium ion exists in the zirconium oxychloride aqueous solution with a molar concentration of 0.2 mol / L.
[0020] In a preferred embodiment, in order to make the prepared mesoporous silica grow regularly into sheets, in addition to adding zirconium oxychloride aqueous solution, a method of adding tetraethyl orthosilicate twice is adopted. In order to make the primary product obtained after its hydrolysis mainly grow longitudinally to form a sheet structure, the addition amount of zirconium oxychloride solution and the interval time between the two additions of tetraethyl orthosilicate are strictly controlled, and the interval time is preferably 55 to 70 minutes.
[0021] In a preferred embodiment, the preferred addition amount of the zirconium oxychloride aqueous solution is 3.8-4.2 g. If the addition amount is too small, a mixed phase will be generated on the surface of the mesoporous silica nanosheets. If the addition amount is too large, the thickness of the sheet increases, and the crossing and stacking of the sheets will become more serious.
[0022] In a preferred embodiment, in order to make the thickness of the obtained nanosheet thinner, a method of adding a pre-prepared hydrochloric acid aqueous solution with the same concentration as the original reaction system is adopted for a second time.
[0023] In a preferred embodiment, the stirring reaction time after the second addition of the pre-made hydrochloric acid aqueous solution is 5 minutes. If the time is too long, it will not only increase the thickness of the mesoporous silica ultra-thin nanosheets, but also make the microscopic morphology of the product irregular.
[0024] In a preferred embodiment, after stopping stirring, the best static reaction time is 3 to 3.5 hours. If it is only static for 1 hour, the reaction is not sufficient and the sheet structure cannot be generated. If it is only static for 2 hours, although the sheet structure has been generated at this time, the reaction is still incomplete, and some small granular impurities will be distributed on the nanosheet. If it is static for 3 to 3.5 hours, the reaction is completely sufficient at this time, and a standard impurity-free mesoporous silica ultra-thin nanosheet will be generated, and the thickness of the sheet also meets the expected requirements. If the static time exceeds 3.5 hours or is more than 4 hours, the generated product is also sheet-like, but the structure is very irregular and the thickness is also increased.
[0025] In a preferred embodiment, the water bath temperature of the reaction system is 30° C., at which time tetraethyl orthosilicate has a suitable hydrolysis rate to form mesoporous silica nanosheets with more stable structure.
[0026] In a preferred embodiment, the hydrothermal temperature is 120-140° C., under which condition a relatively ideal mesoporous structure can be formed in the product.
[0027] In a preferred embodiment, the calcination conditions of the obtained product after drying are: 550° C. for 6 to 8 hours to completely remove the template in the product and keep it in a good mesoporous structure.
[0028] It can be seen that the preparation method of the mesoporous silica ultrathin nanosheets of the present invention has a simple process and is easy to implement, the materials are easily available and have high safety, the product is single and easy to separate, and the cost is low, which is conducive to the industrial production of mesoporous silica ultrathin nanosheets.
[0029] The mesoporous silica ultrathin nanosheet prepared by the present invention is observed under a scanning electron microscope, and its microscopic morphology is a regular hexagonal thin sheet, with an optimal thickness of 49.4nm and an average thickness of 55nm. It has a high specific surface area and good application prospects.
[0030] To further illustrate the method for preparing a mesoporous silica ultrathin nanosheet provided by the present invention, the following examples are provided. Example 1
[0031] 20g of P123 aqueous solution, 60g of deionized water, 4g of zirconium oxychloride aqueous solution, 7g of concentrated hydrochloric acid and 7.5g of glycerol aqueous solution were placed in a 300mL beaker and stirred evenly in a 30℃ water bath. After about 12 to 15 minutes, 3.42g of tetraethyl orthosilicate was added to the mixed solution for the first time while stirring, and the stirring was continued in the water bath. After 1 hour, 0.86g of tetraethyl orthosilicate was added to the solution for the second time while stirring, and the mixture was continued in the water bath. Continue stirring; after 10 minutes, add the mixed solution of 93g deionized water and 7.0g concentrated hydrochloric acid prepared in advance at 30℃ to the above solution while stirring, and continue stirring in the water bath; after 5 minutes, stop stirring the above mixed solution and continue to stand in the water bath at 30℃; after 3 hours, transfer the reaction product to the reactor and put it in a 120℃ oven for hydrothermal treatment; after 24 hours, take out the reactor, stand and cool, filter, dry and calcine at 550℃. The final product is the mesoporous silica ultrathin nanosheet.
Claims
1. A method for preparing mesoporous silica ultrathin nanosheets, characterized in that: The method introduces tetravalent zirconium ions and propylene glycol as inhibitors, adds the silicon source twice and controls the ratio of the two additions to prepare a unique mesoporous silica ultrathin nanosheet with a thickness of less than 100 nm.
2. The mesoporous silica ultrathin nanosheet according to claim 1, characterized in that: The front morphology observed under a scanning electron microscope is a regular hexagon, and the overall structure is a lamellar structure with a thickness of less than 100nm and the optimal thickness can reach about 50nm.
3. The method for preparing mesoporous silica ultrathin nanosheets according to claim 1, characterized in that: The following steps are involved: P123, H2O, zirconium source and glycerol were placed in a beaker under acidic conditions and mixed, and heated in a water bath while stirring; After a period of reaction, TEOS, i.e. tetraethyl orthosilicate, is added to the mixed solution for the first time while stirring, and the reaction continues; After a period of reaction, TEOS is added to the stirred mixed solution for the second time to continue the reaction; After a period of reaction, add the acidic aqueous solution prepared in advance to the stirred mixed solution to continue the reaction; After a period of reaction, stop stirring and let it stand in a water bath to allow the reactants to fully react; After standing, turn on the stirring function of the water bath to fully mix the generated white precipitate with the upper clear aqueous solution, then transfer the solution into a polytetrafluoroethylene liner and place it into a hydrothermal synthesis reactor for hydrothermal treatment. After the hydrothermal treatment, take out the product, wash, filter, dry, and calcine to remove the template agent. The obtained product is the mesoporous silica ultrathin nanosheet as described in claim 1.
4. The preparation method according to claim 3, characterized in that: The acidic condition is generated by adding 6 to 8 g of concentrated hydrochloric acid to the solution. P123 refers to a mixture of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and deionized water, wherein the content of the copolymer is 10% of the total solution, H2O is deionized water, and the zirconium source is an aqueous solution of zirconium oxychloride with a concentration of 0.2 mol / L.
5. The preparation method according to claim 3, characterized in that: The water bath temperature was 30°C and the rotor speed was 1200 r / min.
6. The preparation method according to claim 3 or 8, characterized in that: The reaction time after the first addition of TEOS is 55 to 70 minutes.
7. The preparation method according to claim 3, characterized in that: The reaction time after the second addition of TEOS is 12 to 20 minutes.
8. The preparation method according to claim 3, characterized in that: The acidic aqueous solution added is a mixed solution of hydrochloric acid and deionized water, wherein the amount of hydrochloric acid is consistent with the amount of concentrated hydrochloric acid added to the previous mixed solution, the amount of deionized water is 90-95g, and the temperature of the aqueous solution is 30-33°C.
9. The preparation method according to claim 3, characterized in that: The standing time is 3 hours and the standing temperature is 30°C.
10. The preparation method according to claim 3, characterized in that: The calcination temperature is 550° C. and the calcination time is 5 hours.
Citation Information
Cited By
Preparation method of Pd (OH) 2 / ultrathin spherical two-dimensional SiO2 catalyst as well as product and application thereof
CN120479419A